Pranata Mandiek Anak di Nagari Salareh Aia Kecamatan Palembayan Kabupaten Agam dan Multikulturalisme Budaya Bangsa - Iron Maria Edi; Hasanuddin Hasanuddin; Fadlillah Fadlillah (Dance and Theatre Review, 2022)
The Rule of Mandiek Anak at Nagari Salareh Aia, Palembayan District, Agam Regency, and Nation's Multiculturalism This article is the result of research on the Institution of Mandiek Anak in Nagari Salareh Aia, Palembayan District, Agam Regency, which is a procession of the baka-baki in the Nagari Salareh Aia customary community. The Cultural Studies approach that was carried out on this institution was able to dismantle the form, function, and meaning of Mandiek Anak in the order of the Nagari Salareh Aia customary community. There are two customary community structures in Nagari Salareh Aia known as Langgam, namely Langgam Saripado and Langgam Panghulu Nan Balimo. This institution functions to strengthen kinship, control and social control, education, economy, self-identity, information, social integration, religion, and traditional cultural performances of Nagari Salareh Aia. This institution has an important meaning between the two extended families of the father and his people, as well as the children and their extended family because Mandiek Anak presents the quality of kinship ties that are maintained between the two. The institution of Mandiek Anak is carried out in the nuclear family and clan institution which then extends to other clans because the Bajaj custom from the paternal clan or korong kampung anak involves the relationship between the two clans and other clans in the local customary arrangement. With the linkage of all parties, the institutions that operate Mandiek Anak start from the Batih, Paruik, Kaum, Luhak, and Langgam families within the Nagari Salareh Aia customary community. Mandiek Anak is a national cultural root that still exists and is maintained in the Nagari Salareh Aia indigenous people who are part of the Indonesian Nation's Cultural Multiculturalism which must remain sustainable and alive. Keywords: Mandiek Anak, Style, Multiculturalism